2021
DOI: 10.1097/md.0000000000026156
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of postoperative delirium in general anesthesia patients with hip fracture

Abstract: Delirium is a common postoperative complication of patients with hip fracture, yet the risk factors for postoperative delirium in patients with hip fracture remain unclear. We aimed to evaluate the associated risk factors of postoperative delirium in patients with hip fracture, to provide evidence for formulating coping measures of postoperative delirium prevention and treatment in clinical practice. Patients undergoing surgery for hip fracture from March 1, 2018 to September 30, 2020 in our hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Hypoalbuminemia was another risk factor for POD in patients with hip fracture in our study, which was consistent with Chu’s study (Chu et al, 2021 ) and Kong’s study (Kong et al, 2022 ). Chu et al found that albumin ≤32.26 g/L was an independent risk factor in elderly patients with hip fracture, which was slightly different from Kong’s study (albumin ≤32.26 g/L vs. albumin ≤40 g/L).…”
Section: Discussionsupporting
confidence: 93%
“…Hypoalbuminemia was another risk factor for POD in patients with hip fracture in our study, which was consistent with Chu’s study (Chu et al, 2021 ) and Kong’s study (Kong et al, 2022 ). Chu et al found that albumin ≤32.26 g/L was an independent risk factor in elderly patients with hip fracture, which was slightly different from Kong’s study (albumin ≤32.26 g/L vs. albumin ≤40 g/L).…”
Section: Discussionsupporting
confidence: 93%
“…The drugs used in general anesthesia for hip fracture patients are mainly cerebral vasoconstrictors, which are able to increase cerebrovascular resistance and affect cerebral blood flow, and greater dosage may cause higher risk of unexpected events. In addition, most studies did not demonstrate that age was related to cerebrovascular accidents [ 25 ], but according to the multiple logistic regression in this study, it was found that P < 0.05 at age ≥80 years, which might be explained by the fact that when general anesthesia was a factor to consider, the surgical risk coefficient was significantly higher in elderly patients; especially, those with preoperative multivisceral disease were more likely to trigger cardiovascular and cerebrovascular diseases, so under general anesthesia, age ≥80 years was also a risk factor causing the presence of general anesthesia. If the recovery time after general anesthesia of such patients exceeds 90 min, the involvement of anesthetic drugs, patients' preoperative comorbidities, vital organ failure, and other conditions should also be taken into consideration, and if the delay recovery cannot be explained after excluding all factors, it is necessary to speculate on the possibility of cerebrovascular accidents based on intraoperative blood pressure, heart rate fluctuation, and pupil changes and fully focus on the vital sign observation in the high-risk period to prevent cerebrovascular accidents.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of clinical practice, identifying predictors of POD may ultimately lead to an improved understanding of this condition, and facilitate the development of specific interventions. To aid early recognition, a series of risk factors, including age, polypharmacy, electrolyte disorders, and diabetes, have been proposed for patients with hip fractures [ 6 , 7 , 8 ]. Emerging literature has described the positive roles of glycemic control factors, including glucose variability and glycosylated hemoglobin type A1C (HbA1c) level, in predicting outcomes in older patients.…”
Section: Introductionmentioning
confidence: 99%